RECORD KEEPING PROCESS OF HOMESCHOOLING CHILDRENS’ LEARNING OUTCOMES FOR BUILDING PORTFOLIO - Mardiati, Wiwiet (Journal of Documentation and Information Science, 2018)
Homeschool or family-based education is one form of informal education recognized by the National Education Act in Indonesia. With a wide variety of families running a variety of homeschooling methods, portfolios can be one way to evaluate the learning process of their children at home. The key to build a portfolio is how the portfolio is structured and used in the recordkeeping process of the learning outcomes of everyday children. Therefore, this preliminary study was conducted to get an idea of how homeschool parents aged 7-15 years doing the process of recordkeeping their academic and non-academic activities. Data collection is done by a mixed method. A total of 68 parents responded to an online questionnaire distributed through Facebook and WhatsApp group with the majority having primary school age children (91.2%) and were previously schooled (67.6%) with their daily activities contain academic activities (79.4%) and non-academic (98.1%). In addition, in-depth interviews were also conducted with 6 (six) parents whose children have an interest in sports and the creative worlds. The results showed that almost all respondents recorded their activities by using camera photos for both academic (90.7%) and non-academic activities (86.6%), followed by writings (72.2%) for academic activities, and video recordings (64.2%) for non-academic activities. Obstacles perceived by the respondents generally are (1) consistency of recording and (2) grouping the results of the learning track record in their chosen storage. Although the process of recordkeeping has not been done from the beginning of planning, as the portfolio should be built, from the interviewed respondents, the results of the children>s learning record can be given as material for applying for jobs informally because of the network they have. Nevertheless, 92.6% of respondents stated that they need assistance in preparing the portfolio, such as consultation (76.5%), workshop (76.5%), and seminar (44.1%).